More than Money: The Importance of Social Exchanges for Temporary Low‐Skilled Migrant Workers' Workplace Satisfaction. (28th July 2019) - Chang, Eunmi; Chin, Hyun; Lee, Jeongwon; Chung, Ki‐Seon
Abstract: Research has focused on the happiness of immigrants, but the workplace satisfaction of temporary low‐skilled migrant workers has rarely been explored. By utilizing survey data for two years, 2010 and 2013, along with interviews with migrant workers, we explored how economic or social factors could trigger diverse impacts on the satisfaction of temporary low‐skilled migrant workers in different work environments. Results showed that economic factors triggered more notable impacts in 2010, while the importance of social factors increased with improvements in work environments in 2013. The results indicated that moving motive premises and social exchange theory effectively explain attitudes of temporary low‐skilled migrant workers. Theoretical and practical contributions and suggestions of the results are also included.